GLOBAL ASYMPTOTIC STABILITY FOR A STOCHASTIC COMPETITION AND COOPERATION MODEL OF TWO ENTERPRISES - Xu, Changjin; Liao, Maoxin (Italian Journal of Pure and Applied Mathematics, 2015)
This paper deals with a stochastic competition and cooperation model of two enterprises. Some very verifiable criteria on the global stability of the positive equilibrium of the deterministic system are established. An example with its computer simulations is given to illustrate our main theoretical findings.